Peranan Human Papiloma Virus Dalam Perkembangan Adenokarsinoma Serviks - Rizki Hanriko; Krisna Murti; Rizal Sanif; Muhammad Irsan Saleh (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Cervical adenocarcinoma is a subtype of cervical carcinoma with a poor prognosis and is associated with Human Papillomavirus (HPV) infection. HPV contributes to the development of cervical adenocarcinoma through multiple mechanisms, primarily by modulating molecular pathways that regulate cell growth, survival, and immune responses. To analyze the role of HPV in the development of cervical adenocarcinoma by focusing on the molecular mechanisms involved, through a systematic review of previously published studies. The systematic literature review was conducted in accordance with the PRISMA 2020 guidelines. Literature searches were performed in PubMed Central, Google Scholar, and the Wiley Online Library for articles published between 2015 and 2025. The search strategy used combinations of terms related to the disease, exposure, and molecular pathways, connected with Boolean operators (AND/OR) and tailored to each database. A total of 16 articles met the eligibility criteria and were analyzed using a thematic narrative approach. The synthesis findings indicate that the HPV oncoproteins E6 and E7 play central roles in driving malignant transformation by disrupting cell-cycle regulation and DNA repair. In addition, HPV is known to modulate several keys signaling pathways—PI3K/Akt/mTOR, MAPK/ERK, and Wnt/β-catenin, which contribute to proliferation, invasion, and angiogenesis, inhibit cell death, and promote tumor formation. HPV influences the development of cervical adenocarcinoma through complex interactions involving the E6/E7 oncoproteins, HPV genome integration, and activation of key cellular signaling pathways. Therefore, a deeper understanding of these interactions mechanisms may facilitate the development of more effective, novel molecular therapeutic targets for cervical adenocarcinoma. Keywords: Cervical Adenocarcinoma, HPV, Molecular Pathways.  ABSTRAK Adenokarsinoma serviks merupakan salah satu subtipe karsinoma serviks dengan prognosis yang buruk dan berhubungan dengan infeksi Human Papiloma Virus (HPV). HPV berperan dalam terjadinya adenokarsinoma serviks melalui berbagai mekanisme, terutama memodulasi sejumlah jalur molekular yang mengatur pertumbuhan, kelangsungan hidup, dan respon imun. Untuk menganalisis peran HPV dalam perkembangan adenokarsinoma serviks berdasarkan mekanisme molekuler yang terlibat melalui sistematik review dari berbagai penelitian yang sudah dilakukan. Sistematik literatur review dilakukan dengan mengikuti pedoman PRISMA 2020. Pencarian literatur dilakukan pada basis data PubMed Central, Google Scholar, dan Wiley Library pada artikel yang terbit dalam periode 2015-2025. Kata kunci yang digunakan adalah kombinasi istilah penyakit, paparan, dan jalur molekular yang digabungkan dengan operator Boolean (AND/OR) dan disesuaikan dengan masing-masing database. Sebanyak 16 artikel memenuhi kriteria dan dianalisis secara naratif tematik. Hasil sintesis menunjukan bahwa oncoprotein HPV E6 dan E7 memainkan peranan sentral dalam mendorong transformasi ke arah keganasan melalui gangguan regulasi siklus sel dan perbaikan DNA. Selain itu, HPV juga diketahui memodulasi beberapa jalur persinyalan utama, yaitu PI3K/Akt/mTOR, MAPK/ERK, dan Wnt/β-catenin yang berkontribusi terhadap proliferasi, invasi, angiogenesis, menghambat kematian sel dan memicu pembentukan tumor.  HPV mempengaruhi perkembangan adenokarsinoma serviks melalui interaksi kompleks antara oncoprotein E6/E7, integrasi genom HPV, dan aktivasi jalur-jalur persinyalan seluler kunci. Oleh karena itu, pemahaman yang mendalam terhadap mekanisme interaksi tersebut, dapat membantu pengembangan target terapi molekuler baru yang lebih efektif untuk mengatasi adenokarsinoma serviks. Kata Kunci: Adenokarsinoma Serviks, HPV, Jalur Molecular.